Integrasi Tafsir dan Hermeneutika Dalam Memahami Teks al-Qur’an - Safrodin, Safrodin (Program Studi Ilmu Al-Qur`an dan Tafsir, Fakultas Ushuluddin, UIN Sunan Kudus, 2021)
This study seeks to explain the integration of interpretations (tafsīr) and hermeneutics in understanding the Qur'an, even though the possibility of the integration is still being debated among Muslims. Some Islamic scholars reject it absolutely, some of them accept it absolutely and others accept it with certain limits (muqayyad). The author sees that the hermeneutic perspective should not be avoided in the study of interpretation of the Qur'an, so that the study of interpretation becomes more philosophical, even though both have slightly different characteristics. The science of interpretation (‘ilm tafsīr) grows and develops in the treasures of Islamic thought which is very closely related to tradition, while the hermeneutics develops in a philosophical tradition that highly values freedom of thought more broadly. However, hermeneutics is very likely to be used as one of the approaches or tools in the science of interpretation, especially in understanding the verses of the Qur'an which are in the domain of ta'aqqulī or ghair ta'abbudī and ghair ta'aqqudī like the mu'amalah region whose reach is very wide.